2008
DOI: 10.1142/s0218625x08011986
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophilization of Polyvinyl Chloride Surface by Ozonation

Abstract: The surface modification mechanism of polyvinyl chloride (PVC) by ozonation was investigated to study the selective hydrophilization of PVC surface among other plastics. Infrared analysis confirmed the increase of hydrophilic groups. XPS analysis revealed that the increase was due to the structural change in chlorine group in PVC to hydroxylic acid, ketone, and carboxylic groups by ozonation. This chemical reaction by ozone could occur only for polymers with chlorides in its structure and resulted in the selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 14 publications
0
9
0
1
Order By: Relevance
“…The results obtained indicated that the RMS height slightly decreased from 4.421 to 4.184 nm and from 10.335 to 10.311 nm for rigid and fl exible PVCs respectively. 17 The fourier transform infrared spec- were also detected at 1210-1260 cm −1 as a single bond between O and H and at 1200-1275 cm −1 as an ether bond between C and O. The intensities of these hydrophilic groups increased as a result of ozonation in both types of PVC.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…The results obtained indicated that the RMS height slightly decreased from 4.421 to 4.184 nm and from 10.335 to 10.311 nm for rigid and fl exible PVCs respectively. 17 The fourier transform infrared spec- were also detected at 1210-1260 cm −1 as a single bond between O and H and at 1200-1275 cm −1 as an ether bond between C and O. The intensities of these hydrophilic groups increased as a result of ozonation in both types of PVC.…”
Section: Resultsmentioning
confidence: 93%
“…This could be due to the chloride groups on the surface of PVC being replaced with hydrophilic functional groups, e.g., hydroxyl groups and carboxyl groups. 14,17 Our earlier study also reported the physical surface changes caused by ozonation, as analyzed by atomic force microscopy (AFM). 17 The surface hydrophilicity may increase as a result of decreased surface roughness.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…La reacción química del ozono con el PVC es explicada por Kurose et al (2008). Estos autores afirman que los átomos de cloro presentes en las moléculas de cloruro de vinilo (PVC) son convertidos por la ozonización en ácido hidroxílico, cetona y grupos carboxílicos.…”
Section: Introduccionunclassified